Why Do We Need Media Multitasking? A Self-Regulatory Perspective - Popławska, Agnieszka; Szumowska, Ewa; Kuś, Jakub (Frontiers in Psychology, 2021)
In the digital world of today, multitasking with media is inevitable. Research shows for instance that, on average, American youth spend 7.5 hours every day with media and 29% of that time is spent processing different forms of media simultaneously (Uncapher, et al., 2017). Despite numerous studies, however, there is no consensus whether media multitasking is effective or not. In the current paper, we review existing literature and propose that in order to ascertain whether media multitasking is effective it is important to determine 1) which goal, or goals, are used as a reference point (e.g. acquiring new knowledge, obtaining the highest number of points in a task, being active on social media); 2) whether a person’s intentions and subjective feelings or objective performance are considered (e.g. simultaneous media use might feel productive, yet objective performance might be deteriorated) and finally 3) whether short- or long-term consequences of multitasking media use are considered (e.g. media multitasking might help attain one’s present goals yet be conducive to cognitive strategy leading to lesser attentional shielding of goals). Depending on these differentiations, media multitasking can be seen as both a strategic behavior undertaken to accomplish one’s goals as well as a self-regulatory failure. The article integrates various findings from the area of cognitive psychology, psychology of motivation and human-computer interaction.